Orrore e meraviglia: la narrazione autobiografica di Othello in Desdemona di Toni Morrison (Altre Modernità, 2018)
Toni Morrison's Desdemona (2011) is a theatrical adaptation of William Shakespeare's Othello that illuminates issues of race, gender and cultural hybridity from a peculiar African American perspective. This paper aims to investigate the ways in which Morrison's play draws on both early modern travel writing and African American autobiography in order to challenge prescriptive notions of blackness and whiteness. Morrison draws on a quintessentially African American literary genre and subverts its main rhetorical strategy – that is, sentimentalism – by injecting in it themes and tropes of early colonial discourse. She explores Othello's desire to partake in this discourse and to comply with its rhetorical rules in order to highlight slavery's power to fatally corrupt not only the morals of the slaveholders, but also those of the ex-slaves. The image Morrison gives of Othello contrasts either with the stereotypical noble savage or with the self-reliant slave who righteously triumphs over his morally reproachful master. In Desdemona, Othello is a pitiless soldier dominated by brutal instincts, who perpetrates atrocities, exactly as – and together with – his white comrades. The mutual pleasure that results from their shared crimes proves that, contrary to what happens in traditional African American autobiography, Othello's transition from slave to 'man', from servitude to 'freedom', is a controversial process that brings about misuse of power and a dangerous adherence to the degrading colonial logic of tyranny and possession. Morrison's reversal of sentimentalism compels readers and spectators to reject conventional binary oppositions such as black/white, good/evil, and victim/torturer.